2013
DOI: 10.1089/tmj.2012.0219
|View full text |Cite
|
Sign up to set email alerts
|

Uncompressed High-Definition Videoconferencing Tools for Telemedicine and Distance Learning

Abstract: Uncompressed high-definition (HD) video image quality is superior to compressed HD video provided in most commercially available videoconferencing products. Uncompressed HD videoconferencing tools provide a more immersive experience because there is no reduction of image information and, in most cases, lower latency. Four open source uncompressed video applications are reviewed that have been tested at the National Library of Medicine: three transmitting uncompressed HD video and one transmitting loosely compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Uncompressed High Definition technologies, though not yet ready for broad deployment, can be used in disciplines such as teledermatology in which standard definition video is not satisfactory. 15 Results of this review showed that a very low proportion of papers have mentioned frame rate and image quality of their videoconferencing solutions. Although the overall quality of videoconferencing depends on many factors, 16 reporting a few basic settings of videoconferencing (such as frame rate) under study can roughly indicate the quality of video and audio experienced by the clinicians and/or patients during a clinical video visit.…”
Section: Discussionmentioning
confidence: 99%
“…Uncompressed High Definition technologies, though not yet ready for broad deployment, can be used in disciplines such as teledermatology in which standard definition video is not satisfactory. 15 Results of this review showed that a very low proportion of papers have mentioned frame rate and image quality of their videoconferencing solutions. Although the overall quality of videoconferencing depends on many factors, 16 reporting a few basic settings of videoconferencing (such as frame rate) under study can roughly indicate the quality of video and audio experienced by the clinicians and/or patients during a clinical video visit.…”
Section: Discussionmentioning
confidence: 99%
“…Teledermatology was chosen as the research domain because this study includes testing very high resolution uncompressed high definition video and more standardized, compressed high definition video. The former are just emerging from laboratories and need testing in telemedicine domains where high resolution images are needed [10,11]. Dermatological diagnoses rely on visual examination to a great extent and resolution more be more of an issue than in other medical domains, such as telepsychiatry.…”
Section: Introductionmentioning
confidence: 99%